Segurança do paciente na atenção primária: conhecimento dos profissionais de saúde - Paranaguá, Thatianny Tanferri de Brito (2015)
The general objective was to analyze the effect of an educational program on patient safety, developed by Tele-education, in the knowledge of professionals working in primary care. Study type intervention before and after, conducted with registered health professionals in Telehealth Network of Goiás. Were used self-report instruments, via web and carried out a descriptive statistical analysis. The results showed weaknesses in the knowledge of health professionals on patient safety, in the context of the practice, which subsidized the construction of an educational program which proved satisfactory to the expansion of knowledge about the studied subject. The reports of the incidents revealed the importance of acquiring knowledge on patient safety, to identify occurrences of the various incidents in primary care and highlighted the need to work conceptual aspects with greater depth in order to increase the accuracy of these professionals for the identification and monitoring of incidents arising from care. The study can be used globally, contributing to the diagnosis of knowledge about patient safety, to identify gaps that need to be worked for the management of health services, and the elaboration of educational policies that support the formation of a safety culture and quality in health services, in order to reduce the occurrence of incidents and prevent harm to patients who weeks care in primary care.